Wind Turbine Blade Design with Computational Fluid Dynamics Analysis - YİĞİT , Cemil (International Journal of Computational and Experimental Science and Engineering, 2017)
Although there are many blade profile have been improved for use in aviation and energy sector, there is still needed blade profiles which have higher performance especially the commercial horizontal axis wind turbine efficiency is taken into account. The purpose of this study is to obtain the new blade profiles which have higher lift (CL) and drag (CD) coefficients for wind turbine making geometric modifications on several NACA wing profile systematically. For this purpose, the performance of NACA and developed new profiles have been compared with each other using computational fluid dynamics analysis and it is seen that the new developed profiles have higher performance than NACA profiles. Later on, according to the Blade Element Momentum Theory (BEM Theory) turbine blades are designed with developed new profiles and 3-dimensional CFD analyses are performed. Increase in torque in the wind turbine is determined.